Female entrepreneurs’ strategies to mitigate work-family conflict - Bandeira, Emanuella Lustosa; Cabral, Augusto Cézar de Aquino; Lima, Tereza Cristina Batista de; Ipiranga, Ana Silvia Rocha; Santos, Sandra Maria dos (Contextus - Revista Contemporânea de Economia e Gestão, 2020)
This study analyzed female entrepreneur’s strategies to mitigate work-family conflict through qualitative and descriptive research using interviews with nine businesswomen. The results show that sharing roles by hiring professionals to help run the business, outsourcing domestic work, and family management are the main mitigation strategies. The study contributes to the incipient discussion about the positive effects of motherhood for the field of management, highlighting the reduction of conflicts, and business’ professionalization and growth. The research suggests public policies designed to help coordinating family and work demands, contributing to the development of women-led enterprises.